Asymptotic Methods in the Theory of Perforated Membrane of Nonhomogeneous Structure - Andrianov, I.V.; Starushenko, G.A. (Engineering Transactions, 1995)
Homogenization equations are constructed for perforated membranes. Asymptotic methods are used for solving the cell problem.